PENERAPANA PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN PRESTASI BELAJAR IPA SISWA KELAS IV SD 40 KOTA ERNATE - Munir Latukau (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
Through the implementation of STAD (Student Teams Achievement Divisions) in learning with the main topic of energy and its transformation, students quickly absorbed the teaching material presented by the teacher. This learning model was felt to be very efficient. After its implementation, students quickly and enthusiastically received the material presented by the teacher. The results of the evacuation showed that student scores exceeded the minimum standard scores set by the teacher for science subjects. To encourage increased student learning achievement, teachers must seriously implement it. When compiling the device, teachers must carefully analyze it, including its weaknesses and shortcomings.